Positive psychology and tourism: a systematic literature review - Garcês, Soraia (2019)
This study aims to outline the relationship between Positive Psychology and tourism through a systematic literature review. Tourism seeks to increase the wellbeing of people, and wellbeing is a crucial variable in Positive Psychology which in turn aims to understand and promote people's potential. This research used as search terms 'Positive Psychology', 'wellbeing', 'happiness', 'tourism', 'visitor' and 'travel', terms which were applied through the Online Knowledge Library. The inclusion/exclusion criteria led to a sample of 49 references which were then individually analyzed. Results showed a recent increase in studies focused on the relationship between the variables, Europe being in the lead. Overall, policies are important for tourism development; tourism promotes wellbeing for residents and tourists; entrepreneurs have an innovative opportunity in wellbeing; and nature is linked to wellbeing. Implications and suggestions for future studies are presented.